Development of acute lung injury after the combination of intravenous bleomycin and exposure to hyperoxia in rats. Issue 5 (May 1987) - Hay, J G; Haslam, P L; Dewar, A; Addis, B; Turner-Warwick, M; Laurent, G J
Abstract : Pulmonary toxicity is an important adverse effect of bleomycin treatment. Very little is known of the mechanisms underlying the development of lung injury, especially after intravenous administration, or how it can be modulated. In this study acute lung injury induced by bleomycin has been examined in rats by assessment of alveolar lavage cell profiles, histological examination, and measurement of the total pulmonary extravascular albumin space. Intratracheal instillation of bleomycin 1.5 mg resulted in a severe pneumonitis with influx of inflammatory cells into the alveoli as assessed by alveolar lavage, oedema of the alveolar walls, and up to an eight fold increase in the total pulmonary extravascular albumin space, maximal at 72 hours. Intravenous bleomycin 0.15-5 mg produced no detectable injury when assessed in these ways. Exposure to hyperoxia (40-90%) after intravenous bleomycin, however, induced lung injury similar to that produced by intratracheal bleomycin. A much more severe injury followed administration of intravenous bleomycin after an exposure to hyperoxia, which itself resulted in lung injury; but lung injury was still detectable after bleomycin when the exposure to hyperoxia was insufficient to induce changes in control animals. Lung injury was not observed when the exposure to hyperoxia preceded bleomycin treatment. These results indicate the importance of oxygen in the pathways leading to acute lung injury following intravenous bleomycin. We conclude that exposure to oxygen might induce lung injury during and after bleomycin treatment, and suggest that in these circumstances oxygen therapy should be kept to a minimum.